Analysis of prehistoric brown earth paleosols under the podzol soils of Exmoor, UK. Issue 5 (6th April 2020) - Carey, Christopher; White, Hayley; Macphail, Richard; Bray, Lee; Scaife, Rob; Coyle McClung, Lisa; Macleod, Alison
Abstract: The deforestation of the upland landscapes in southwest Britain during prehistory is an established archaeological narrative, documenting human impacts on the environment and questioning the relationship of prehistoric societies to the upland landscapes they inhabited. Allied to the paleoenvironmental analyses of pollen sequences, which have provided the evidence of this change, there has been some investigation of prehistoric paleosols fossilized under principally Bronze Age archaeological monuments. These analyses identified brown earth soils that were originally associated with temperate deciduous woodland, on occasion showing evidence of human impacts such as tilling. However, the number of analyses of these paleosols has been limited. This study presents the first analysis of a series of pre‐podzol brown earth paleosols on Exmoor, UK, two of which are associated with colluvial soil erosion sediments before the formation of peat. This study indicates these paleosols are spatially extensive and have considerable potential to inform a more nuanced understanding of prehistoric human impacts on the upland environments of the early‐mid Holocene and assess human agency in driving ecosystem change.